Synthesis and Magnetic Properties of Coordination Polymer of Cu(II)-Schiff Base - Wang, Lin; Bi, Jian-Hong; Wang, Hong-Liang (Asian Journal of Chemistry, 2011)
A copper(II) coordination polymer with the composition [CuL]4(ClO4)8(H2O)8(CH3OH)0.5 {L = (6Z,15Z)-N1',N2'-bis[amino(pyridin-2-yl)methylene]oxalohydrazide} has been synthesized by self-assembly and characterized by IR spectra, elemental analysis and TG measurement. The magnetic properties indicates that there is a weak antiferromagnetic interactions between the copper(II) ions in molecule of the coordination polymer.